PHYTOTHERAPY TREATMENT OF URINARY TRACT INFECTION IN CHILDREN - T.S. Voznesenskaya; E.K. Kutafina (Union of pediatricians of Russia, 2007)
Urinal system infection is one of the most frequent bacterial infection diseases in childhood. approximately 30% of children suffer from relapses of urinal infections. Optimal therapy is very important to avoid the risk of kidney cicatrisation because of urinal infection. Last years specialists pay more attention to phyto medications, since they have both a complex action and a significantly fewer side effects as compared to synthetic medications. We have studied the action of Kanefrom phytomedication upon the urinal infection processes of children. We have found a reduced frequency of relapses among children with acute pyelonephritis, who were treated with the above medication for 3 months after a course of antibiotics. Children whose therapy was terminated after a course of antibiotics. Key words: pyelonephritis, urinal infection, prophylaxis, children, phytotherapy.